Analysis of Desktop-Based Interactive Learning Media Using Smart Apps Creator App For Computer Recognition In SDN 006 Tempuling - Vitriani Vitriani; Rahmad Al Rian; maria marta rina (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2022)
Computer recognition is very important and needs to be taught to students. Especially among learners in primary level se Kolah, in reality there is still a great lack of computer recognition and a delay among students in getting to know computers. The results of the observations made by the students were very difficult and confusing in using computers to complete computer-based national assessment questions, so in this activity the accompanying teacher asked the questions. This research aims to assist students in learning about the community for conducting computer-based national assessment activities for conducting computer-based national assessment activities using a learning medium. The research method used is the research and development (R&D) method and the development model using the ADDIE model which has five phases, namely analysis, design, development, implementation and evaluation. Data is collected using a questionnaire (Likert scale). The results of the evaluation of the desktop-based learning media for computer recognition were tested by media experts. The materials expert received a score of 88% in the 'very decent' category and the media expert received a score of 84% in the 'sanguine' category, while the student respondent test received a score of 80 in the 'excellent' category. Based on the research findings, it was concluded that interactive learning media for computer recognition is highly applicable to SDN 006 Tempuling.